Framing Analysis of Israel-Palestine Conflict News on Online Media Detik.com and Republika.co.id - Hanief, Lalita; Ainani, Muhammad (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2024)
The conflict between Israel and Palestine has become a humanitarian tragedy and is in the spotlight of the world's mass media. This research seeks to determine the framing of the coverage of the Israeli-Palestinian conflict based on Zhongdang Pan and Gerald M. Kosicki's analysis model. Two leading online media, detik.com and republika.co.id, were selected as research objects because they have a long history, different audiences, and contrasting approaches to reporting, which reflect their views and handling of the Israeli-Palestinian conflict. It is a qualitative study; data was collected through observation, documentation, and literature study. The analysis results found that detik.com and republika.co.id syntactically present the facts clearly; the script fulfills the 5W + 1H elements with credible source quotes. The thematic structure of detik.com emphasizes the number of victims due to Israeli attacks on Palestine. The rhetorical structure of detik.com contains idioms and displays photos relevant to the news content. The thematic structure of republika.co.id emphasizes the form of Israeli attacks on the Jabalia Refugee Camp. The rhetorical structure contains idioms and photos relevant to the news content. Detik.com frames the news by using the figurative word